Numerical Evaluation of the Effects of Increasing Ratio of Cropped to Uncropped Width on Dry Drainage Efficiency in Salty Soils†. (4th December 2017) - Soltani, Masoud; Rahimikhoob, Ali; Sotoodehnia, Abbas; Mendicino, Giuseppe; Akram, Mojtaba; Senatore, Alfonso
Abstract: Sustainable agriculture can contribute to food security in arid and semi‐arid regions if soil salinity in the root zone is kept under control. Recently, experts have been concentrating their research towrds alternative and environmentally friendly solutions. In this study, dry drainage was evaluated as a sustainable and cost‐effective alternative technique, by means of both field experiments and a numeric approach based on the HYDRUS‐2D modelling environment. Results showed that soil salinity in the cropped area increased from the soil surface to the bottom, and soil salinity movement (transport direction) was from the cropped to uncropped area. Increasing the ratio of cropped to uncropped width led to an increase in soil salinity of the cropped root zone and lack of stabilization of salinity concentration. Results of modelling showed that there are no significant differences between observed and modelled data, even though HYDRUS‐2D simulated soil water content better than soil salinity. Averages of performance indices for simulated soil water content (SE = 0.08, NRMSE = 0.133) were better in comparison with simulated soil salinity (SE = 0.28, NRMSE = 0.262). Soil surface salinity in the cropped area increased 2.7 times (from 2.1 to 5.7 dS m −1 ) during the experiment for equal cropped to uncropped width (1 (cropped): 1 (uncropped)), and by increasing cropped width (2 (cropped): 1 (uncropped)) it increased 7.5 times (from 2.3 to 17.3 dS m −1 ). Copyright © 2017 John Wiley & Sons, Ltd.